1982
DOI: 10.1073/pnas.79.14.4424
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of beta-adrenergic receptors in senescent rats: a study using an irreversible binding antagonist.

Abstract: The drug used in this study, bromoacetylalprenololmenthane, has the ability to bind and block irreversibly a-adrenergic receptors. The drug was bound to membranes prepared from hearts, lungs, and brains of both senescent and young rats with a similar affinity. When this drug was injected into rats in nontoxic doses (up to 70 mg/kg), up to 90% of P-adrenergic receptors were irreversibly blocked 4 hr after injection, whereas the injection of similar amounts of (±)-alprenolol was without effect on receptor number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…When agonist induced desensitization is permitted to continue, the internalized receptors are partly destroyed (Harden 1983), and receptor synthesis is required for restoration of the full number of surface receptors. This required 1-2 months in rat lung when ß-adrenoreceptors were irreversibly blocked by covalent bindings (Pitha et al 1982); -a comparable time span was found for ß-adrenoceptor regeneration in MNL of patients IV and V after tumour excision. Receptors in the high affinity state seem to be synthesized preferen¬ tially, as isoproterenol-induced cAMP accumula¬ tion is restored faster than the entire ß-receptor population.…”
Section: Discussionmentioning
confidence: 69%
“…When agonist induced desensitization is permitted to continue, the internalized receptors are partly destroyed (Harden 1983), and receptor synthesis is required for restoration of the full number of surface receptors. This required 1-2 months in rat lung when ß-adrenoreceptors were irreversibly blocked by covalent bindings (Pitha et al 1982); -a comparable time span was found for ß-adrenoceptor regeneration in MNL of patients IV and V after tumour excision. Receptors in the high affinity state seem to be synthesized preferen¬ tially, as isoproterenol-induced cAMP accumula¬ tion is restored faster than the entire ß-receptor population.…”
Section: Discussionmentioning
confidence: 69%
“…Since the turnover rate of cardiac /3-receptors is normally slow (Pitha et al, 1982), de novo synthesis may not be utilized under physiological conditions. Pathological states, however, may interfere with the adequacy of receptor recycling through several mechanisms involving the energetics of the cell, microtubular assembly, lysosomal integrity, ionic gradients, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report described aging-related decreases in the regeneration of visceral beta-adrenergic receptors after their irreversible blockade (13), thus suggesting one possible mechanism for the observed age-related deficits in receptor up regulation. A vehicle and decapitated at various times.…”
mentioning
confidence: 94%